2000
DOI: 10.1002/(sici)1097-4628(20000418)76:3<368::aid-app12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion polymerization of an epoxy-acrylate emulsion stabilized with polyacrylate. II. Using the results of statistically designed experiments to deduce a possible polymerization mechanism

Abstract: Epoxy-acrylate composite emulsions such as the one in this study can be used as metal coatings, etc. Many factors can influence the final quality of the product, and it is the aim of this study to highlight some of these factors. Statistically designed experiments were performed to investigate the influence of monomer level, the polymeric dispersant level, epoxy level, and the initiator level on particle size (light scattering), particle size distribution, and fractional conversion. It was found that the monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The data presented in Table 1 revealed that increasing butyl acrylate content increases particle diameter in the first set of experiments concerning polymer I-polymer V. This agrees well with other findings obtained by Kiatkamjornwong and Kongsupapsiri [13] . In the second set of experiments, it was found that increasing the glycidyl methacrylate monomer ratio increased particle size as reported by Wet Ross et al [14] Evaluation of the Emulsion Latices-treated Cotton Fabrics Different types of finishing agents are used to impart different types of properties to the fabrics. The choices of finishing agent depend on the type of fiber to be processed and the desired finishing.…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…The data presented in Table 1 revealed that increasing butyl acrylate content increases particle diameter in the first set of experiments concerning polymer I-polymer V. This agrees well with other findings obtained by Kiatkamjornwong and Kongsupapsiri [13] . In the second set of experiments, it was found that increasing the glycidyl methacrylate monomer ratio increased particle size as reported by Wet Ross et al [14] Evaluation of the Emulsion Latices-treated Cotton Fabrics Different types of finishing agents are used to impart different types of properties to the fabrics. The choices of finishing agent depend on the type of fiber to be processed and the desired finishing.…”
Section: Morphological Characteristicsmentioning
confidence: 99%
“…The use of experimental design to study hybrid waterborne coatings has been described by the authors 7,8 as well as in a recent work by Ranjbar et al 9 and serves as a powerful tool to optimize and investigate which factors affect the rate of polymerization in these kinds of emulsion systems. The combination of experimental design and feed forward neural networks (ffNN) to model emulsion polymerization has been described by Delfa et al 10.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental design is a statistical tool of fundamental importance to improve a given process, since higher reliability conditions and lower costs can be delineated 12. For instance, this technique has been used for the study of polymerization reactions 13–17…”
Section: Introductionmentioning
confidence: 99%